Evaluation of storage stability of refrigerated buffalo meat coated with hydrothermally treated potato starch incorporated with thyme (Thymus vulgaris) and ginger (Zingiber officinale) essential oil - Sangam Dahal; Basanta Kumar Rai; Anish Dangal; Kishor Rai; Prekshya Timsina; Ramesh Koirala; Sanjay Chaudhary; Pankaj Dahal; Tanka Bhattarai; Angelo Maria Giuffrè (AIMS Agriculture and Food)
The present study was carried out to prepare thyme essential oil (TEO) and ginger essential oil (GEO)-incorporated edible starch coating on buffalo meat to extend its refrigerated shelf-life. Edible coatings incorporated with antimicrobials can act as an active packaging system for the preservation of meat using biopolymers and plant-based essential oils. Buffalo meat samples were coated by hydrothermally treated starch solution incorporated with thyme and ginger essential oil at five different proportions (total of 2.5% of starch solution). A total of five treatments (S1, S2, S3, S4, and S5) along with two controls (S6 and S7) were subjected to microbiological [total viable count (TVC), Staphylococcus aureus count, psychrotrophic bacteria count (PTC), and coliform count] and physico-chemical analyses such as thiobarbituric acid reactive substance (TBARS) value, total volatile basic nitrogen (TVBN) content, extract release volume (ERV), metmyoglobin (Met-Mb), pH, weight loss, and water activity at 0, 3, 6, 9, and 12 days of storage. These metrics were compared between days and between treatments. Compared with the uncoated control (S7), S4 decreased TVC by 2.60 log, and S5 decreased PTC, Staphylococcus aureus, and coliform by 4.71 log, 1.18 log, and 3.01 log, respectively, in 12 days. S4 reduced TBARS and TVBN by 46.14% and 27.86%, respectively, while S5 increased the ERV by 40.94% in 12 days when compared to S7. Metmyoglobin content, pH, ERV, and TVBN were found to have a high correlation with TVC, while pH was found to have a high correlation with TVBN and ERV. It can be concluded that the increase in TEO concentrations on starch coating increases the ability of buffalo meat to resist microbiological as well as chemical spoilage.